Response to laboratory selection for darker and lighter body color phenotypes in Drosophila melanogaster: correlated changes for larval behavioral traits. Issue 4 (4th July 2021) - Singh, Divya; Ramniwas, Seema; Kumar, Girish
Abstract : Laboratory selection of stress-related traits in adult flies of Drosophila melanogaster has resulted in contrasting phenotypes but coevolution of larval traits has received lesser attention. The hypothesis whether laboratory selection of adult body melanization to derive dark and light body color lines exhibit covariation of larval behavioral traits of D. melanogaster was tested. The larvae of selected light lines showed longer foraging path, higher relative feeding rate, and lower pupation height whereas opposite trend values were observed for the larvae of selected dark lines. The larvae of dark lines stored significantly higher level of carbohydrates while light lines stored lipids. Larval pupating behavior of selected dark and light lines also showed divergence. For water balance-related traits, significantly higher trait values in the larvae of selected darker lines were found while lighter body color lines showed greater starvation resistance. Thus, laboratory selection of adult body melanization led to correlated selection responses for larval behavioral traits which are adaptive in nature.